2003
DOI: 10.2337/diabetes.52.4.1041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Autofluorescent Property of Hemoglobin-Advanced Glycation End Product as a Long-Term Glycemic Index of Diabetes

Abstract: Current methods for measuring long-term glycemia in patients with diabetes are HbA 1c and advanced glycation end products (AGEs), which are estimated by phenyl boronate affinity chromatography and competitive enzyme-linked immunosorbent assay, respectively. In this study, we hypothesize that the intrinsic fluorescence property of hemoglobin-AGE (Hb-AGE) may be a simple, accurate, and therefore better index for longterm glycemic status due to its highly specific nature and longer half-life. To establish this co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
(14 reference statements)
0
15
0
Order By: Relevance
“…Formation of AGE has been observed in vivo in several long-living proteins such as lens crystalline and collagen affected by diabetes mellitus. 9,11) Some radical species including oxygen are considered to play an important role in these processes. 10) Hence compounds that scavenge radical species are expected to prevent the formation of AGEs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of AGE has been observed in vivo in several long-living proteins such as lens crystalline and collagen affected by diabetes mellitus. 9,11) Some radical species including oxygen are considered to play an important role in these processes. 10) Hence compounds that scavenge radical species are expected to prevent the formation of AGEs.…”
mentioning
confidence: 99%
“…Recently, many reports have suggested that these complications are caused by the formation of advanced glycation end products (AGEs), which are generally formed through Amadori-type compounds from proteins and glucose. [7][8][9][10][11] AGEs are postulated to be physiological markers of the Maillard reaction in a biological system. Formation of AGE has been observed in vivo in several long-living proteins such as lens crystalline and collagen affected by diabetes mellitus.…”
mentioning
confidence: 99%
“…19,20 has investigated glycated hemoglobin fractions by fluorescence measurements. It was showed that in vitro glycated hemoglobin gave the maximum intensity of emitted light at 345 nm upon excitation at 308 nm.…”
Section: Introductionmentioning
confidence: 99%
“…3 Most methods quantify hemoglobin A1c, defined as hemoglobin A with glucose attached to the NH2-terminus valine of one or both beta chains. Over the last years various optical methods for monitoring of free glucose and glycated hemoglobin levels have been investigated, such as near-infrared spectroscopy 4-13 , optical coherence tomography 14 , polarimetry 15 , Raman spectroscopy [16][17][18] and fluorescence 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Examples include hemoglobin [2][3][4] , interferon-␤ 1b [5] , highand low-density lipoproteins [6,7] , antithrombin III [8] , enzymes [9] , insulin [10,11] , collagen [12][13][14][15][16] , ␣ -crystallines of lenses [17] , fibronectin [18,19] , laminin [20] , peripheral nerve myelin [6,21] , and IgG and human serum albumin [22] .…”
Section: Introductionmentioning
confidence: 99%